Myasthenic crisis appearing after resection of intracardiac ectopic thymoma with superior vena cava syndrome - Satoshi Takebayashi; Yasuji Yoshikawa; Masato Morita; Ryotaro Nagashima; Yuichi Nakazono; Shinji Miyamoto (Surgical Case Reports)
Abstract Background We describe herein an extremely rare case of intracardiac ectopic thymoma—only two pure cases have been reported to date—associated with myasthenia gravis, an infrequent complication of ectopic thymoma. Case presentation A 71-year-old woman with superior vena cava syndrome was found to have a large mass mainly located in the right atrium. Tumor resection under cardiopulmonary bypass was performed. The pathological diagnosis was type AB ectopic thymoma. The postoperative course was complicated by progressive respiratory failure, and she was diagnosed with myasthenic crisis based on clinical signs and the edrophonium test. The patient recovered and was weaned from prolonged mechanical ventilation after receiving intravenous immunoglobulin, and was subsequently discharged uneventfully. Conclusions This is the first report of myasthenic crisis due to intracardiac ectopic thymoma. Residual thymoma is a risk factor for the development of post-thymectomy myasthenia gravis, and long-term follow-up is required.